Teachers’ scientific approach implementation in inculcating the students’ scientific attitudes - Dewi Masithoh (Jurnal Prima Edukasia, 2018)
The study aimed at attaining an overview on teaching experiences by means of guided inquiry model of the scientific approach in order to inculcate the scientific attitudes among the students of Luqman Al Hakim International Integrated Islamic Primary School Yogyakarta. The study was a qualitative research using the ethnographic classroom approach. The subjects in this study were the headmaster, the homeroom teachers of Grade 4A students, and the Grade 4A students. In collecting the data, the researchers conducted interview, observation, and documentation. Then, the instruments that the researchers employed were the interview guidelines and the observation guidelines. The data in this study were analyzed using Lankshear and Knobel models and the analysis also included the data that had been attained from both the observation and the interview. In order to test the data validity, the researchers conducted the subject triangulation and the method triangulation. The findings in this study thus revealed that the teaching activities that make use of the scientific approach consists of seven strands of learning cycles and these strands include the spiritual, moral, intellectual, physical, interpersonal, cultural, and social aspects. Each aspect has specific purpose and, as a result, by implementing each aspect the students will have the scientific attitudes similar to those owned by a scientist in solving their problems. The recounted teaching experiences, which made use of the scientific approach, have shown similarities in that teaching activities become more meaningful if they are conducted realistically with various learning activities both inside and outside the classroom. The constraints in the application of the scientific approach are varying the teachers’ ability in understanding the scientific approach, varying the learning styles and the learning abilities, and varying the learning process for the students who need special assistance.